Nanoscaled mechanical properties of cement composites reinforced with carbon nanofibers - Barbhuiya, Salim; Chow, Pengloy (mdpi, 2017)
This paper reports the effects of carbon nanofibers (CNFs) on nanoscaled mechanical properties of cement composites. CNFs were added to cement composites at the filler loading of 0.2 wt % (by wt. of cement). Micrographs based on scanning electron microscopy (SEM) show that CNFs are capable of forming strong interfacial bonding with cement matrices. Experimental results using nanoindentation reveal that the addition of CNFs in cement composites increases the proportions of high-density calcium-silicate-hydrate gel (HD-CSH) compared to low-density CSH gel.It was also found that the inclusion of CNFs increases the compressive strength of cement composites.